Implementação de um fluxo dinâmico de dificuldade e viabilização de acessibilidade para o jogo “As Aventuras de Amaru” - BRITO, Yvan Pereira dos Santos (2019)
In Brazil there are a large number of illiterate people. According to IBGE's 2015 statistics, about 8% of the Brazilian population aged 15 years or older are illiterate. Although public policies are implemented in the most precarious regions of the country, their efficiency does not seem to be enough to zero these data or at least to reduce these numbers to a satisfactory level. With this, several educational projects were developed to overcome these problems and one of these projects was conceived from a partnership between psychologists and computer professionals generating the game called "The Adventures of Amaru", with the purpose of helping children in reading and writing using tasks that present letters, syllables, and pictures. For this work a system of balancing difficulties of the tasks performed in the game was developed with the purpose of balancing the tasks that are assigned to the children; and adaptations in the interactions with the game, adding a tool of detection of movements called Leap Motion, where the user can use motions of a coupled tool in your hand to guide the Amaru through the level if the keyboard and mouse are not the best option. In addition, changes have been made to the game's graphical interface for better interaction with the user and the expert who will handle the application.